Preservation of Snake Fruit Cultivar Pondoh (Salacca edulis Reinw.) at Cold Temperature Storage - Albertus Carolus Dito Wratsongko; Anang Mohamad Legowo; Ahmad Ni'matullah Al-Baarri; Mulyana Hadipernata; Wisnu Broto (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2019)
This study was done to preserve snake fruit cultivar Pondoh cold temperature storage. Snake fruits was obtained from Turi, Sleman, Yogyakarta and transferred to the laboratory with the aseptic condition. The sortation based on the visual method was used to collect the proper snake fruit. The cleaning using aseptic cloth was done prior to storage. The snake fruit was collected individually in refrigeration containers at temperatures of 10±5˚C. The storage was done for 30 days and it was stopped until appearance of physical damage in snake fruit. The result indicates that the storage using this method might extend the shelf-life of snake fruit until 28 days. However, snake fruit was hardly to peeled and dry. It can be concluded that cold temperature might extend the shelf-life of snake fruit.